Legislators Qualifications in Pakistan Under Islamic Constitutional Provisions - AllahRakha, Naeem (Journal of Human Rights, Culture and Legal System, 2025)
Legislators’ qualifications play a vital role in preserving the integrity, legitimacy, and credibility of democratic governance. In Pakistan, the Constitution outlines specific requirements for candidates in Article 62, which are based on Islamic principles. However, the election laws do not provide clear procedural or definitional guidance for applying these provisions. This study examines the constitutional and Islamic foundations of legislators’ qualifications, interprets these provisions in light of Islamic teachings, and compares them with eligibility criteria in other democratic jurisdictions. The findings show that Pakistan’s electoral framework does not include explicit mechanisms to evaluate a candidate’s good character, Islamic knowledge, or moral conduct. Key terms such as good character, Islamic duties, and major sins remain undefined. This lack of clarity creates legal uncertainty, causes inconsistent enforcement, and raises concerns about fairness, transparency, and equal political rights. The absence of precise definitions also allows arbitrary or politically motivated interpretations, which weaken the rule of law. The comparison reveals that Egypt, Iran, Turkey, and Indonesia use more explicit legal or institutional mechanisms to determine candidate eligibility. The study concludes that lawmakers should clarify constitutional terms in election laws to strengthen legal certainty, ensure consistent application, and improve democratic governance.